A Study of Chinese Banks’ Cross-border Mergers and Acquisitions Performance: A Case of Industrial and Commercial Bank of China - Liu, Mingye (2009)
Globalization is the main trend for all the companies, which provides a good opportunity for companies to involve in the global market competition. Cross-border merger and acquisition (M&A) becomes one of the popular methods of foreign direct investment (FDI). China’s financial market has a great development especially in recent 10 years. Many Chinese companies grow fast and become stronger in the domestic market in these 10 years, so that more and more companies would like to involve in the overseas transactions to seek the new market. In the banking industry, although many Chinese banks begin to operate the cross-border M&A transactions, due to the limited experience and knowledge they are still freshmen in the global market. Generally, the main reason for companies to operate the M&A deals is to enhance shareholders’ wealth and promote companies’ development.